Progress in Understanding Cystic Fibrosis - Sriramulu, Dinesh (IntechOpen, 2017)
Congenital defects in humans are of greater concern, and in that line, cystic fibrosis (CF) has been one of the most complex diseases posing treatment challenge till date. Though it is a chronic condition, CF is closely associated with dysfunction of various organ systems of the human body, which in turn results in secondary infections by microbes. Decades of research by scientists worldwide has narrowed down the cause of CF to a single target gene. But the complexity of the disease is the prime impediment to finding a single-shot cure. Fortunately, the multidisciplinary approach toward understanding and management of the CF condition has certainly increased the level of life expectancy among CF patients. In particular, the "omics" and the "systems biology" approach have greatly widened the focal area for better understanding of the disease. This book includes a collection of interesting chapters contributed by eminent scientists around the world who have been striving to improve the life of those affected by CF.